Prognostic values of the diastolic index as a marker of chronic heart failure with preserved left ventricular ejection fraction - V. V. Syvolap; V. A. Lysenko (Zaporožskij Medicinskij Žurnal)
Chronic heart failure (CHF) remains the leading cardiovascular disease worldwide. The prevalence of CHF with preserved ejection fraction (HFpEF) among other CHF phenotypes continues to rise. Despite a large number of studies focused on diagnosing this CHF phenotype, information on additional parameters for the verification of this disease phenotype are accumulating, and their prognostic values remain to be fully addressed. One such echocardiographic marker is the diastolic index that has proven its prognostic value in diagnosing HFpEF in the Japanese population. However, questions have been raised over the possibility of applying this parameter in the European population.